1996
DOI: 10.1007/s002620050305
|View full text |Cite
|
Sign up to set email alerts
|

Anti-idiotype cancer vaccines: past and future

Abstract: Anti-idiotypic antibodies (Ab2) binding to the antigen-combining site of antitumor antibodies (Ab1) can induce anti-anti-idiotypic antibodies (Ab3) that specifically bind to the tumor antigen recognized by Ab1. Furthermore, Ab2, mimicking tumor antigens, have been shown to induce anti-anti-idiotypic proliferative T lymphocytes of the helper and suppressor type, as well as cytotoxic lymphocytes. The immunomodulatory activities of Ab2 have been demonstrated both in animals and in patients. The demonstration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Whereas the immunological implications of the HAMA response have been investigated in great detail [7][8][9], the potential therapeutic effect of the HAHA response is largely unknown. In this regard the induction of anti-idiotypic network responses may even be involved in mediating effector mechanisms [10][11][12]. These effects can be explained based on the anti-idiotypic network theory postulated by Jerne [13].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the immunological implications of the HAMA response have been investigated in great detail [7][8][9], the potential therapeutic effect of the HAHA response is largely unknown. In this regard the induction of anti-idiotypic network responses may even be involved in mediating effector mechanisms [10][11][12]. These effects can be explained based on the anti-idiotypic network theory postulated by Jerne [13].…”
Section: Introductionmentioning
confidence: 99%
“…19 This suggested that antibody immunotherapy may be able to induce T cell responses against an original target antigen. Other protocols immunized actively with preformed Ab2 antibodies of xenogeneic or human origin to the same effect, [47][48][49] inducing Ab3 and T3 by single step responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relevance of preclinical studies of targeting this antigen in passive and active immunotherapy (with MAbs, anti-idiotypic antibodies, and recombinant antigen; reviewed in Herlyn et al, 1982Herlyn et al, , 1995Herlyn et al, , 1996 for clinical trials in patients has been difficult to determine in the absence of information on normal tissue expression of the antigen homologue in animals. We demonstrate here that an antigen homologous to the human gastrointestinal carcinoma-associated antigen GA733 is expressed by normal intestine and liver of mice, rats and nonhuman primates, as determined by immunohistoperoxidase staining of tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of experimental passive and active immunotherapy targeting the human GA733 antigen in mice (Herlyn et al, 1982(Herlyn et al, , 1997) must be interpreted with caution, keeping in mind the immunological differences between the human antigen and its homologue. Thus, passive immunotherapy with MAb C017-lA and GA733 (Herlyn et al, 1982 and active immunotherapy with anti-idiotypic antibodies mimicking the GA733 or C017-IA epitope or with recombinant GA733 antigen (reviewed in Herlyn et al, , 1996 have been performed in mice which, in contrast to humans, do not express the C017-lA and GA733 epitopes on normal tissues. The differences in the GA733 epitope tissue expression between mice and humans might explain why treatment of mice with MAb GA733 was not accompanied by toxicity , whereas this MAb showed dose-limiting toxicity to gastrointestinal organs in colon cancer patients .…”
Section: Discussionmentioning
confidence: 99%